POST COVID-19 RECOVERY STRATEGIES: REVITALIZING SAUNG ANGKLUNG UDJO BUSINESS MODEL - Diani Mustika Prianti; Idqan Fahmi; Sufrin Hannan (UNIVERSITAS PAKUAN, 2022)
Saung Angklung Udjo is one of the cultural tourism objects and attractions in Bandung. Saung Angklung Udjo is currently facing competition issues, such as the growth of various tourism businesses in Bandung and decreasing level of public awareness of culture, especially Sundanese culture. Furthermore, the COVID-19 pandemic has changed the landscape of the tourism industry as well as the behavior of consumers or tourists who have adapted to new normal conditions. This research aims to formulate a new business model which can be used as a business development strategy for Saung Angklung Udjo in the future. This descriptive qualitative research used purposive sampling as the technique of determining respondents, based on Business Model Canvas (BMC) approach, which was equipped with SWOT analysis and Blue Ocean Strategy (BOSS). The findings showed that creating a hydroponic nursery center by utilizing vacant land, collaborating with various modern art communities, adapting the creative process of Angklung performance videos, and running e-tourism programs will attract broader customer segments (generation Z and millennials), as well as more, deserve of the revenue stream. This research still has many limitations, in terms of research objects there are still many that can be examined, such as service quality, customer satisfaction, cost analysis.